Determination of Air Cargo Performance: Analysis of Revenue Management, Terminal Operations, and Aircraft Loading (Air Cargo Management Literature Review) - Rifqi Raza Bunahri; Dhian Supardam; Hadi Prayitno; Cris Kuntadi (Dinasti Publisher, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews three issues, namely: revenue management, terminal operations, and aircraft loading which affect the performance of air cargo. The results of this literature review article are: 1) There are revenue management problems that can affect air cargo performance; 2) There are problems with terminal operations that can affect the performance of air cargo; and 3) There are problems with aircraft loading which can affect the performance of air cargo.